2003
DOI: 10.1063/1.1586467
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity, critical current density, and flux pinning in MgB2−x(SiC)x/2 superconductor after SiC nanoparticle doping

Abstract: We investigated the effect of SiC nano-particle doping on the crystal lattice structure, critical temperature Tc, critical current density Jc, and flux pinning in MgB2 superconductor. A series of MgB2−x(SiC) x/2 samples with x = 0 to 1.0 were fabricated using in-situ reaction process. The contraction of the lattice and depression of Tc with increasing SiC doping level remained rather small due to the counter-balanced effect of Si and C co-doping. The high level Si and C co-doping allowed the creation of intra-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
91
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 25 publications
(27 reference statements)
18
91
4
Order By: Relevance
“…This is a typical characteristic for HTS in which weak links are the dominating factor for current flow. We do not have this weak link characteristics even at higher doping levels for non-magnetic dopants [16]. 20%SiC addition to MgB 2 not only showed no such weak link feature but had a strong enhancement effect on J c (H) [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a typical characteristic for HTS in which weak links are the dominating factor for current flow. We do not have this weak link characteristics even at higher doping levels for non-magnetic dopants [16]. 20%SiC addition to MgB 2 not only showed no such weak link feature but had a strong enhancement effect on J c (H) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Kuzmann et al [3] and Guo et al [16] suggested possible Fe substitution in the Mg site in the MgB 2 lattice [3]. Because these techniques were applied to an entire sample the claim of Fe substitution for Mg was inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The authors' group found that doping of MgB 2 with nanoparticle SiC can significantly enhance J c in high fields, with only slight reductions in T c up to a doping level as high as 30% of B. 10 Compared to the undoped sample, the J c for the 10 wt % SiC doped sample increased by more than an order of magnitude at all temperatures and in the high field region. The exceptional properties of SiC as a dopant have been verified by a number of groups over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…This might be expected since the primary role of SiC is to increase the H irr and H c2 . Nevertheless some increases in pinning have also been seen [14][15][16][17] , but not in the present case at higher temperatures and lower fields.. …”
Section: Resultsmentioning
confidence: 64%
“…An anisotropy factor of about 1. 4 12,13,14 have studied the effects of nano-Si doping 14 , nano-carbon doping 15 , and carbon nanotube doping 16,17 on the properties of MgB 2 strands. Glowacki 18,19 has also been pursuing PIT MgB 2 , with useful demonstrations particularly with regard to cables and shielding.…”
Section: Introductionmentioning
confidence: 99%